Registrasi Ulang Bagi Penerima Manfaat Pensiun Yang Berbasis Mobile - Bambang Sukowo; Yudo Devianto (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Re-registration activities are routine activities that aim to ensure that Pension Beneficiaries are still entitled to Pension Benefits in accordance with applicable regulations. In addition, this activity is also useful for updating data from Pension Beneficiaries. In re-registration, a Pension Beneficiary is required to complete a “Pension Benefit Validation Form” and must be validated by the Head of the local RT / RW (Head of the Domicile Environment) or a Pension Representative at the local branch. In the current research, we will try to make a model or design of an application that can later assist in the implementation of online re-registration activities. The problem that exists today is that there is no application that can help carry out these activities online. The problem that can be formulated in this research is how to produce a solution that can help solve problems that exist today. In solving existing problems, it is limited in making models or designing applications that will help solve the problem, if there is time to support the application to be made and implemented at the same time, if it will not be continued in further research.